Ending the HIV Epidemic: New York's Quest to Become the First State to Reduce HIV Prevalence. (July 2020) - Morne, Johanne E.; Tesoriero, James M.; Martin, Erika G.; Birkhead, Guthrie S.; Holtgrave, David R.; Hagos, Karen; Zucker, Howard
In 2014, New York State became the first jurisdiction to launch a statewide initiative to end AIDS by reducing the number of persons living with HIV for the first time since effective HIV treatment became available. The Ending the Epidemic (ETE) initiative encompasses (1) identifying and linking undiagnosed persons with HIV to care, (2) retaining persons with HIV in care, and (3) facilitating access to preexposure prophylaxis for persons at risk for acquiring HIV. We used a framework for public health program implementation to describe key characteristics of the ETE initiative, present progress toward 13 ETE target metrics, and identify areas in need of increased programming. We provide evidence suggesting that New York State is on track to end AIDS as an epidemic by the end of 2020. As of 2017, 76% of progress toward our primary ETE target had been achieved. Substantial progress on several additional metrics critical to decreasing HIV prevalence and to improving the health of persons living with HIV had also been achieved. Lessons learned included the following: (1) ETE-based programming should be tailored to each jurisdiction's unique political and social climate, HIV epidemiology, fiscal resources, and network of HIV service providers; (2) key stakeholders should be involved in developing ETE metrics and setting targets; (3) performance-based measurement and timely communication to key stakeholders in real time are essential; and (4) examining trends in HIV prevention and care metrics is important for developing realistic ETE timelines.